The Image of Women in Advertisements for Iraqi Satellite Channels - Jawad Mohammed Ameen Issa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The study aimed to identify the advertised image for women presented by Iraqi satellite channels, and analyze it in terms of form and content. The analytical method is used for analyzing collected data. Through a content analysis of television advertisements broadcasted by Iraqi television represented by the (Al-Iraqiya, Al-Sharqiya and Al-Sumeria) satellite channels, the researcher chose the study sample. The researcher conducted a comprehensive survey of the advertisements of the three channels. The total number of advertisements for the three studied Iraqi channels was (282) advertisements with a total time of (170) minutes and (25) seconds. The findings of the study identified the fact that the image which is presented about women by the above channels is a traditional and stereotyped. The negative image of women in television advertisements may be partially due to the fact that most of those employees in the advertising sections are men, therefore the advertisements that present the image of women do not present the reality of women as much as they present the men’s vision about women. The negative and traditional image will continue unless the advertisers change their vision towards women, without this change, women will remain hostage to their traditional image. The women in advertisements used as an attractive means for many advertisers who promote their goods through their presence in most advertisements, but their role often limited to a housekeeper, which draws image of inferiority of women in a stereotyped and traditional manner. Regarding women’s age, the study shows, that the younger women occupy the first place in participation in advertisements in all three chandelles, likewise, the proportions of the categories of depicted excitement of women in advertisements is high, which is considered as a bad employment of women in advertisements, and mainly serves the interests of the advertiser, which has negative affect on women’s image in general. The study shows also that the channels occupy in their advertisement’s women of high economics level, accordingly they ignore women of lowest economics and social level.